Effects of isothermal storage on grain structure of Cu/Sn/Cu microbump interconnects for 3D stacking. (November 2019) - Panchenko, Iuliana; Wolter, Klaus-Juergen; Croes, Kristof; De Wolf, Ingrid; De Messemaeker, Joke; Beyne, Eric; Wolf, M. Juergen
Abstract: The crystal orientation and grain distribution of Cu6 Sn5 and Cu3 Sn intermetallic compounds (IMCs) in miniaturized solid-liquid interdiffusion (SLID) interconnects for 3D stacking were investigated. Therefore Cu/Sn microbumps with a diameter of 15 μm on top die (metal height 5.4 μm/3.6 μm) and Cu microbumps with a diameter of 25 μm on bottom die (metal height 9.5 μm) were used for bonding and subsequent thermal storage. The effect of the storage time (varied from 10 min to 96 h) and storage temperature (150, 240 and 260 °C) on the grain structure formation was investigated by Electron Backscatter Diffraction (EBSD). After the initial Cu6 Sn5 scallops have grown together, the corresponding Cu6 Sn5 layer only consists of one or two grains, which are orientated with 〈10−11〉 and 〈2−1−12〉 directions parallel to the IMC growth direction (perpendicular to substrate or Cu layer). The Cu3 Sn IMC showed small columnar grains in its early growth stage, which develop into grains with a polygonal shape due to coarsening effects. Cu3 Sn grains are orientated randomly at the early growth stage and tend to be orientated mostly with 〈10−10〉 and 〈2−1−10〉 parallel to the IMC growth direction at higher temperatures and longer storage times. Highlights: Grain structure of Cu/Sn interconnects with Ø15 μm was investigated. The influence of storage time and temperature on grain structure was investigated. Preferred grain orientations of Cu6 Sn5 and Cu3 Sn grains were found.